Digital gangrene in an adolescent with psoriasis. - Belgaumkar, V.A.; Nile, S.P.; Pradhan, S.N.; Dange, K.; Darkase, B. (European Journal of Pediatric Dermatology, 2024)
Psoriasis is associated with an increased risk of cardiovascular disease and atherothrombosis, caused by the combination of systemic inflammation and metabolic abnormalities. The case of an adolescent with extensive psoriasis dating back many years who underwent digital gangrene was presented. Anti-inflammatory and anticoagulant therapy together with secukinumab halted the progression of gangrene and improved psoriasis.